2022
DOI: 10.3390/jcm11123564
|View full text |Cite
|
Sign up to set email alerts
|

Association between Timing of Epinephrine Administration and Outcomes of Traumatic Out-of-Hospital Cardiac Arrest following Traffic Collisions

Abstract: The effects of epinephrine administration timing on patients with out-of-hospital cardiac arrest (OHCA) following traffic collisions are unknown. We analyzed the 2013–2019 All-Japan Utstein Registry data of 2024 such patients aged ≥18 years who were resuscitated by emergency medical service (EMS) personnel or bystanders and then transported to medical institutions. Time from 119 call to epinephrine administration was classified into quartiles: Q1 (6–21 min), Q2 (22–26 min), Q3 (27–34 min), and Q4 (35–60 min). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…No clear benefit for prehospital ROSC, in-hospital survival or short-term survival could be identified. An additional retrospective observational study explored outcomes amongst 2024 patients who sustained a blunt TCA following road traffic collision and were treated with adrenaline [18 ▪ ]. Similar to findings from the PARAMEDIC2 study [19], the investigators found a time dependent relationship on survival relating to the timing of adrenaline administration.…”
Section: Treatmentmentioning
confidence: 77%
“…No clear benefit for prehospital ROSC, in-hospital survival or short-term survival could be identified. An additional retrospective observational study explored outcomes amongst 2024 patients who sustained a blunt TCA following road traffic collision and were treated with adrenaline [18 ▪ ]. Similar to findings from the PARAMEDIC2 study [19], the investigators found a time dependent relationship on survival relating to the timing of adrenaline administration.…”
Section: Treatmentmentioning
confidence: 77%
“…According to the American Heart Association, epinephrine is a recommended medication for treating cardiac arrest; [15] however, its therapeutic effects in TCA remain controversial. [10] In a prospective study, Hosomi et al [16] investigated the eff ect of epinephrine administration at different time points after traumatic out-of-hospital cardiac arrest. It included a total of 2,024 adult patients.…”
Section: Pre-and Intra-arrest Prognostic Factors Aff Ecting Survivalmentioning
confidence: 99%